Conference at Memorial Hall, London : Emergency resolution on civil warfare in Spain
014_0044_001 CONFERENCE AT THE MEMORIAL HALL, LONDON, JULY 20, 1936. on Means Test "A" copy. EMERGENCY RESOLUTION. Civil Warfare In Spain. The Conference, representing the Trade Union, Labour and Co-operative Movement in Great Britain, expresses its profound concern over the outbreak of civil warfare in Spain, at the instigation of the reactionary Fascist forces which were decisively repudiated by the electors at the recent General Election, and their power broken. The Conference declares its confidence in the will of the Spanish Government and the organised Labour Movement behind it, to resist successfully this renewed attack, and pledges all practical support to our Spanish comrades in their struggle to defend freedom and democracy in Spain. 292/946/14/44